Study of Metabolic Adaptation of Red Yeasts to Waste Animal Fat Substrate - Szotkowski, Martin; Byrtusova, Dana; Haronikova, Andrea; Vysoka, Marie; Rapta, Marek; Shapaval, Volha; Marova, Ivana (Microorganisms, 2019)
Carotenogenic yeasts are non-conventional oleaginous microorganisms capable of utilizing various waste substrates. In this work, four red yeast strains (Rhodotorula, Cystofilobasidium, and Sporobolomyces sp.) were cultivated in media containing crude, emulsified, and enzymatically hydrolyzed animal waste fat, compared with glucose and glycerol, as single C-sources. Cell morphology (cryo-SEM (cryo-scanning electron microscopy), TEM (transmission electron microscopy)), production of biomass, lipase, biosurfactants, lipids (gas chromatography/flame ionization detection, GC/FID) carotenoids, ubiquinone, and ergosterol (high performance liquid chromatography, HPLC/PDA) in yeast cells was studied depending on the medium composition, the C source, and the carbon/nitrogen (C/N) ratio. All studied strains are able to utilize solid and processed fat. Biomass production at C/N = 13 was higher on emulsified/hydrolyzed fat than on glucose/glycerol. The production of lipids and lipidic metabolites was enhanced for several times on fat; the highest yields of carotenoids (24.8 mg/L) and lipids (54.5%/CDW (cell dry weight)) were found in S. pararoseus. Simultaneous induction of lipase and biosurfactants was observed on crude fat substrate. An increased C/N ratio (13-100) led to higher biomass production in fat media. The production of total lipids increased in all strains to C/N = 50. Oppositely, the production of carotenoids, ubiquinone, and ergosterol dramatically decreased with increased C/N in all strains. Compounds accumulated in stressed red yeasts have a great application potential and can be produced efficiently during the valorization of animal waste fat under the biorefinery concept.
Keywords: biosurfactants; lipase; carotenoids; ergosterol; lipids; ubiquinone; carotenogenic yeasts